Marjory Fleming and Child Authors: The Total Depravity of Inanimate Things - Langbauer, Laurie (Romanticism and Victorianism on the Net, 2009)
Marjory Fleming was a child diarist who wrote during the Romantic period; her diary was published during the Victorian era. Her text and its reception offer a test case for how “thing theory,” as synthesized by Bill Brown, might provide a theoretical approach that productively reconsiders the categories of “the child” and the child author.